O sentimento de professores e professoras em relação à sua profissão: um estudo nos anos iniciais da educação básica - Silva, Maria Manoela de Oliveira da (Brasil, 2023)
The present study is a research that describes and analyzes the feelings of male and female teachers who work in basic education in the initial years in public schools in the city of Manaus in relation to the profession "Teacher". Quite idealized, the teacher's daily life is sometimes reported in a very different way from the reality of a complex, globalized and technological world, which is why the feeling of the teacher in relation to his/her profession needs to be highlighted . Given this perspective, the following questions were asked about the feelings of the teachers interviewed: how are the feelings in relation to the students, their working conditions, their initial training, their autonomy and pedagogical practice, their leisure time, their salary and how they feel in society. When analyzing how the teacher feels being this professional and what conditions are favorable and unfavorable for this professional exercise, the existing correlation between the collected responses was notorious, even in different schools in the state of Amazonas. The answers related to favorable and unfavorable feelings were quite balanced, so that favorable feelings are commonly related to students, initial training, didacticpedagogical autonomy. On the other hand, unfavorable feelings are mostly related to working conditions, workload, salary and how this professional feels in society